Public-private co-lending: Evidence from syndicated corporate loans - Fotak, Veljko; Lee, Haekwon (Journal of Banking & Finance, 2020)
Co-lending by private-sector and government-owned lenders accounts for over one-tenth of all syndicated-loan funding to corporate borrowers from 1980 to 2010. Co-lending is often rationalized as a mean to impose market discipline on government-owned lenders. We investigate whether that is really the case, or whether political distortions affect “mixed” syndicates including both private and government-owned lenders. We find that mixed syndicates allocate more loans to government-connected firms than private syndicates do. Further, loans from mixed syndicates have lower spreads, longer maturities, less collateral, and fewer covenants. Terms are most favorable when borrowers are “connected.” Firms borrowing from mixed syndicates show a decline in profitability and valuation in subsequent years, suggesting loans are inefficiently allocated. The evidence is consistent with political distortions in mixed lending. Results are driven by domestic government lenders: loan by syndicates including foreign government-owned lenders resemble more closely private-sector loans, both in allocation and loan terms.